Moment redistribution versus neutral axis depth in continuous PSC beams with external CFRP tendons. (15th April 2020) - Lou, Tiejiong; Peng, Chengming; Karavasilis, Theodore L.; Min, Di; Sun, Wei
Highlights: Global redistribution of PSC beams with external CFRP tendons is evaluated. Using solely the neutral axis depth for redistribution quantification is inadequate. Modifications of CSA, BSI and EC2 equations are proposed. Abstract: The neutral axis depth is adopted by many codes of practice as an indicator of flexural ductility to quantify moment redistribution in continuous prestressed concrete (PSC) beams. Moment redistribution, however, does not only depend on ductility but also on differences in stiffness along the length of the beam. Therefore, the effectiveness of using solely the neutral axis depth for redistribution quantification needs to be further evaluated. This study examines moment redistribution against neutral axis depth in two-span PSC beams with external CFRP tendons by applying a validated finite element model. The main variable is the content of non-prestressed reinforcement either at the positive or negative moment zone to generate varying stiffness differences between critical sections. The study shows that the use of neutral axis depth as a key parameter is inadequate when quantifying moment redistribution in these beams. Modifications of CSA, BSI and EC2 equations are proposed by introducing a parameter reflecting the impact of stiffness difference. The proposed equations show much better fit to the actual redistribution than that provided by equations in current design codes.